AN INTEGRATED APPROACH OF INTERPRETIVE STRUCTURAL MODELING (ISM) AND ANALYTIC HIERARCHY PROCESS (AHP) IN DEVELOPING INSTITUTIONAL SYSTEM OF THE BEEF CATTLE INDUSTRY - Rimbun Sumarsono (Agriekonomika, 2016)
This study is aimed to knowing Structuring the sub element of Institutional System of Beef Cattle Industry, The methods used for data collection is by distributing questionnaires, interviews with experts and literature studies. Results of questionnaires and interviews with experts used to construct a hierarchy of election strategy Beef Cattle industry development. Preparation of hierarchy elections industrial development strategy Beef Cattle using AHP technique The formulation of a model institutional system Beef Cattle industry development with key elements in the element's goal is to realize a strong institutional element is the need for government support, elements of the perpetrator is a trader. While the key elements in the benchmarks is the increasing diversification of products Beef Cattle, element of constraint is the weak institutional system, lack of government support for industrial development Beef Cattle and the lack of guidance to the Breeders. For elements of the desired changes to the industrial development Beef Cattle is the formation of an independent group of cattle at the planting site Beef Cattle